2000
DOI: 10.2466/pr0.2000.87.3f.1053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison: Attitudes toward Homosexuality of International and American College Students

Abstract: Using the Index of Attitudes Toward Homosexuals to study the attitudes of 34 Asian students and 32 American students toward lesbians and gay men showed these Asian students were more likely to harbor homophobic attitudes than these American students. There were no significant sex differences between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Vietnamese Americans with higher levels of acculturation had greater levels of positive attitudes toward homosexuality. Although previous research concerning acculturation and homophobia that specifically involves the Vietnamese American community is nonexistent, the finding is consistent with other studies examining acculturation (e.g., Lippincott et al, 2000;Meston et al, 1998). Further, the finding that specific acculturative variables (e.g., number of years the participant had lived in the U.S.) related to their attitudes toward homosexuality is consistent with Hypothesis 1.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Vietnamese Americans with higher levels of acculturation had greater levels of positive attitudes toward homosexuality. Although previous research concerning acculturation and homophobia that specifically involves the Vietnamese American community is nonexistent, the finding is consistent with other studies examining acculturation (e.g., Lippincott et al, 2000;Meston et al, 1998). Further, the finding that specific acculturative variables (e.g., number of years the participant had lived in the U.S.) related to their attitudes toward homosexuality is consistent with Hypothesis 1.…”
Section: Discussionsupporting
confidence: 87%
“…It also appears that Westerners have less negative attitudes toward homosexuals than do Asians. A study by Lippincott, Wlazelek, and Schumacher (2000) found that Asian international students were more likely to have significantly higher levels of discomfort with homosexuals, as compared to U.S. students. Additionally, Meston, Trapnell, and Gorzalka (1998) found that Asians who were born or had a longer residency in a Western country like Canada were not as likely to have negative attitudes toward homosexuality.…”
mentioning
confidence: 99%
“…For the scale evaluation process, we chose to rate the quality of evidence related to the AERA/APA/NCME domains (content/validity/reliability/internal structure) in Likerttype scale. The instruments were rated on a 10 point-scale, punctuating-regardless of the number of studies-if they Rolfs, & Pucell (2007) Nursing students and faculty teachers 4 Cole, Reece, & Lindeman (2005) Health students 5; 10 Span & Vidal (2003) Undergraduate students 3; 4 Burt & DeMello (2002) Undergraduate students 5; 7 Sakalli (2002) Turkish undergraduate students 2; 3; 6; 10 Sakalli & Ug urlu (2002) Turkish undergraduate students 2; 3; 7; 8 Guth, Hewitt-Gervais, Smith, & Fisher (2000) Undergraduate and graduate students 9 Lippincott, Wlazelek, & Schumacher (2000) Asian and American undergraduate students 5 Sakalli & Ug urlu (2001) Turkish undergraduate students 2; 3; 8 Schlub & Martsolf (1999) Nurse students 3 Jome & Tokar (1998) Male undergraduate and graduate students 3; 5 Roderick, McCammon, Long, & Allred (1998) Undergraduate students 3; 4 Berkman & Zinberg (1997) Social workers 3; 4 Monroe, Baker, & Rollb (1997) Men (unspecified) 5; 7 Adams, Wright, & Lohr (1996) Heterosexual men 7 Dunkle & Francis (1996) Undergraduate students 3 Hogan & Rentz (1996) Undergraduate students and staff 3 Matchinsky & Iverson (1996) Undergraduate students 3 Riggle, Ellis, & Crawford (1996) College students 7 Pain & Disney (1995) Australian undergraduate students 4; 6; 8; 10 Patel, Long, McCammon, & Wuensch (1995) College students 3 Smith (1993) Psychiatric nurses 5 Hudson & Ricketts (1980) Undergraduate students 1; 2; 3; 5; 6; 8; 10 Attitudes Toward Lesbians and Gays Scale presented evidence in each of the domains described in Table 1, with a reservation that in the last two items (i.e., temporal stability and internal consistency) the scales punctuated if they presented studies that showed good evidence (>.70).…”
Section: Resultsmentioning
confidence: 99%
“…That homophobic attitudes and behaviors are exhibited toward homosexuals all over the world has been put forward by many research studies (Furnham & Saito, 2009;Altemeyer, 2001;Lippincott, Wlazelek, & Schumacher, 2000;Weishut, 2000;Pratte, 1993). Although there are various scientific studies on homosexuality in Turkey, the number is limited.…”
Section: Da Vid Publishing D Examination Of Students' Attitudes Towarmentioning
confidence: 99%